Extraordinary long range order in self-healing non-close packed 2D arrays - Quint, Stefan B.; Pacholski, Claudia (Soft matter, 2011)
Non-close packed two-dimensional arrays of hydrogel microspheres with exceptional long range order are fabricated by exploiting the remarkable properties of hydrogels such as tunable solubility and self-healing. By addition of alcohol hydrogel microspheres self-assemble at the air/liquid interface into highly crystalline domains which can be merged using mechanical force.
Gesehen am 23.01.2023